DISPARITY OF JUDGES' DECISIONS AGAINST CLASS I NARCOTIC DISTRIBUTORS IN THE JURISDICTION OF THE PEKANBARU DISTRICT COURT BASED ON LAW NUMBER 35 OF 2009 ON NARCOTICS - Ariyanto, Yuli; Kadaryanto, Bagio; Harahap, Irawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
ABSTRACT Article 114 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, which states that it regulates sanctions for people who without rights or against the law offer for sale, sell, buy, receive, act as intermediaries in buying and selling, exchange, or hand over Class I Narcotics.” Research objectives: to analyze the disparity in judges' decisions against Class I Narcotics dealers in the Pekanbaru City area based on Law Number 35 of 2009 concerning Narcotics, to formulate the causal factors; to find efforts to overcome it. Research methods: sociological legal research, legislative approach and case approach; research location: Pekanbaru Police; population and samples from relevant sources; data sources are primary, secondary and tertiary; data collection techniques are observation, structured interviews and document/literature studies; data analysis is qualitative; the conclusion is inductive. The results of the study are that the implementation of the intended disparity has not been carried out properly. The conclusion is First, the implementation has not been good, proven by the disparity in 6 court decisions for perpetrators who are distributors of methamphetamine narcotics from 2021 to 2023 where the disparity cannot be justified. Second, the factors causing the disparity are from the legislative factors, law enforcement officers, facilities/facilities and the community. Efforts to overcome this are From the legislative factors, the disparity in judges' decisions that are not oriented towards achieving justice and legal benefits for the wider community, should not be carried out by judges so that there are no complaints; conduct socialization of the Criminal Code which regulates the Classification of Perpetrators (Dader); judges also refer to the decision of the Supreme Court of the Republic of Indonesia No. 1386 K/Pid.Sus/2011 dated August 3, 2011 to avoid disparity in decisions that do not provide justice. From the law enforcement factor, the Public Prosecutor takes legal action; the judge also issues a verdict based on the facts of the indictment prepared by the Public Prosecutor based on the facts that occurred; splitting (splitting of case files) is done if the role or weight of the evidence is different in a case. From the facility factor, namely the advocate with the local court conducting legal socialization regarding the importance of the presence of an advocate. From the community factor, namely the community finds out about each role of the perpetrator; the community is given legal socialization regarding matters that affect the severity of the crime in the judge's verdict; the judge is really careful in analyzing the consequences caused by the perpetrator; The defendant presents mitigating witnesses at the trial; The defendant/defendant's legal advisor takes legal action. Keywords: Dealers, Narcotics, Disparity ABSTRAK Pasal 114 ayat (1) Undang–Undang Nomor 35 Tahun 2009 tentang Narkotika, yang menyatakan bahwamengatur sanksi bagi orang yang tanpa hak atau melawan hukum menawarkan untuk dijual, menjual, membeli, menerima, menjadi perantara dalam jual beli, menukar, atau menyerahkan Narkotika Golongan I.” Tujuan penelitian: untuk menganalisis disparitas putusan hakim terhadap pelaku pengedar Narkotika Golongan I di wilayah Kota Pekanbaru berdasarkan Undang–Undang Nomor 35 Tahun 2009 tentang Narkotika, untuk merumuskan faktor penyebabnya; untuk menemukan upaya mengatasinya. Metode penelitiaan: penelitian hukum sosiologis, pendekatan perundang–undangan dan pendekatan kasus; lokasi penelitian: Polresta Pekanbaru; populasi dan sampel dari narasumber relevan; sumber data adalah primer, sekunder dan tersier; teknik pengumpulan data adalah observasi, wawancara terstruktur dan studi dokumen/kepustakaan; analisis data adalah kualitatif; kesimpulannya induktif. Hasil penelitian adalah Implementasi disparitas yang dimaksud belum terlaksana dengan baik. Kesimpulannya adalah Pertama, implementasinya belum baik dibuktikan terdapat disparitas terhadap 6 putusan pengadilan bagi pelaku yang merupakan pengedar dalam Narkotika jenis sabu– sabu tahun 2021 sampai 2023 dimana disparitas tidak tidak dapat dibenarkan. Kedua, Faktor penyebab disparitas dari faktor perundang-undangan, aparat penegak hukum, sarana/ fasilitas dan amsyarakat. Upaya mengatsinya ialah Dari faktor perundang-undangan, disparitas putusan hakim yang tidak berorientasi pada tercapainya keadilan dan kemanfaatan hukum bagi masyarakat luas, jangan dilakukan oleh hakim supaya tidak ada komplain; melakukan sosialisasi hukum KUHP yang mengatur mengenai Klasifikasi Pelaku (Dader); hakim juga mengacu putusan Mahkamah Agung RI No. 1386 K/Pid.Sus/2011 tanggal 3 Agustus 2011 untuk menghindari disparitas putusan yang tidak memberikan keadilan. Dari faktor aparat penegak hukum, Jaksa Penuntut Umum melalukan upaya hukum; hakim menjatuhkan vonis juga berdasarkan fakta dakwaan yang disusun oleh Jaksa Penuntut Umum berdasarkan fakta yang terjadi; splitzing (pemecahan berkas perkara) dilakukan jika peran maupun berat barang bukti berbeda dalam suatu tindak perkara. Dari faktor sarana fasilitas yaitu yaitu advokat dengan pengadilan setempat melakukan sosialisasi hukum terkait pentingnya kehadiran advokat. Dari faktor mayarakat yaitu masyarakat mencari tahu tentang masing-masing peran pelaku; masyarakat diberikan sosialiasi hukum terkait hal-hal yang mempengaruhi berat ringannya pidana dalam vonis hakim; hakim benar-benar cermat dalam menganalisis akibat yang disebabkan oleh pelaku; Terdakwa mengadirkan saksi yang meringankan di persidangan; Terdakwa/ penasehat hukum terdakwa melakukan upaya hukum.Kata Kunci: Pengedar, Narkotika, Disparitas